Multicultural Islamic Education Through Syi’iran Bluk Gebluk: A Case Study At The Grogolan Taklim Council, Pasuruan, Indonesia - Mashabi, M. Ali; Marzuki, Ahmad; Nasir, Moh. (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study aims to identify the values of multicultural Islamic education contained in the Shi’iran Bluk Gebluk tradition and analyze the socio-religious transformation it causes. Oral traditions have a strategic role in inheriting Islamic educational values, especially in the context of multicultural societies. The approach used is qualitative with a case study method at the Grogolan Rembang Taklim Council, Pasuruan. Data were obtained through interviews, participatory observations, and documentation, then analyzed using the Miles and Huberman model. The results of the study show that Syi’iran Bluk Gebluk contains the values of tolerance, mutual cooperation, respect for differences and the Book of Risalatul Islam by KH. Zainal Abidin as the main source of Shi’iran also contains Islamic teachings that are oriented towards social justice and collective ethics, making Shi’iran a means of religious education that is contextual, reflective, and loaded with multicultural values of equality, harmony (tawazun), social justice, mutual respect, openness and dialogue in a form that can be accepted by the wider community. Shi’iran has shifted the way of thinking of society from the model of "reciting the book" to a more fun, grounded and inclusive "reciting syai’r". This transformation touches on cognitive, affective, and behavioral dimensions, which brings religion closer to the reality and needs of society. This research contributes to the development of an Islamic education model based on local wisdom. Further studies are recommended to explore the implementation of these values in the formal education curriculum.